Peran Dinas Kelautan dan Perikanan Provinsi Sumatera Barat dalam Mengatasi Bagan Tangkap Ikan di Perairan Danau Singkarak - Lia Angraini; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2019)
This study investigated the Role of the Department of Marine and Fisheries of West Sumatra Province in Overcoming Fish Catch Charts in Lake Singkarak. The purpose of this study was to describe the role, constraints and efforts of the Agency of Marine and Fisheries of West Sumatra Province in overcoming illegal fishing (using floating net catcher, called “Jaring Apung” or “Bagan”) in Lake Singkarak. This was a qualitative research with descriptive analytical methods. This research was conducted in the Subdistrict of X Koto Singkarak, Solok Regency. Primary data were obtained from interviews and observations, while secondary data were obtained from documentation studies. The informants of this research consisted of the Head of the Capture Fisheries Division, the Head of the Sea Space Management and Supervision of SDKP Agency, Community Leaders and the fishing community. The results of this study indicated that: the role of the Department of Marine and Fisheries of West Sumatra Province was not implemented well in overcoming the illegal fishing (using floating net catcher) in the Lake Singkarak. The fishing communities around the lake still operated the illegal fishing. There were some internal and external constraints faced by the Department of Marine and Fisheries of West Sumatra Province in overcoming this issue. Related agencies had attempted to provide guidance such as providing socialization, counseling, and fostering the awareness of fishing communities, to provide environmentally friendly fishing gear, and to stop illegal fishing equipment which was still operated by the fishing communities.